2017
DOI: 10.4317/jced.54040
|View full text |Cite
|
Sign up to set email alerts
|

Solubility and pH of bioceramic root canal sealers: A comparative study

Abstract: BackgroundThis study compared the solubility and the pH of different root canal sealers in vitro.Material and MethodsBioRoot™RCS, TotalFill BC Sealer, MTA Fillapex, SealapexTM, AH Plus, EasySeal, Pulp Canal Sealer™ and N2 were tested. Similar specimens were prepared using ring molds with an internal diameter of 20 ± 0,1 mm and a height of 1,5 ± 0,1 mm and digitally weighted to register the mass of each specimen before and after immersion in distilled water. Solubility was determined after 24 hours and statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
57
1
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 23 publications
13
57
1
8
Order By: Relevance
“…Różnice w metodyce dotyczą również przechowywania próbek, ich wielkości oraz postaci, w jakiej materiały umieszczano w roztworze (postać niezwiązana względnie związana). Podobnie jak w badaniu własnym próbki inkubowano w tym samym roztworze przez cały okres badania, nie wymieniając go na nowy po wykonaniu pomiaru [16,32,33], choć wielu autorów po rejestracji pH umieszczało próbki w świeżym roztworze o pH zbliżonym do obojętnego [23,24,27,30], a inni w ogóle nie podali informacji na ten temat [25,31].…”
Section: Rycina 1 Zmiany Ph W Czasie Ocenianych Uszczelniaczyunclassified
See 1 more Smart Citation
“…Różnice w metodyce dotyczą również przechowywania próbek, ich wielkości oraz postaci, w jakiej materiały umieszczano w roztworze (postać niezwiązana względnie związana). Podobnie jak w badaniu własnym próbki inkubowano w tym samym roztworze przez cały okres badania, nie wymieniając go na nowy po wykonaniu pomiaru [16,32,33], choć wielu autorów po rejestracji pH umieszczało próbki w świeżym roztworze o pH zbliżonym do obojętnego [23,24,27,30], a inni w ogóle nie podali informacji na ten temat [25,31].…”
Section: Rycina 1 Zmiany Ph W Czasie Ocenianych Uszczelniaczyunclassified
“…W cytowanych badaniach próbki umieszczano w wodzie, gdy uszczelniacze były niezwiązane. Natomiast w niektórych badaniach dotyczących właściwości alkalizujących uszczelniaczy kanałowych ocenie poddano związane materiały, wykonując z nich z użyciem matryc próbki w formie krążków lub walców o różnej średnicy i wysokości (5 × 1 mm; 8 × 1,6 mm; 10 × 1 mm; 7,75 × 1,5 mm, 20 × 1,5 mm) [16,25,27,32,33].…”
Section: Rycina 1 Zmiany Ph W Czasie Ocenianych Uszczelniaczyunclassified
“…TotalFill BC has adequate physicochemical properties, but appears to be soluble (Poggio et al . , Tanomaru‐Filho et al . , Colombo et al .…”
Section: Introductionmentioning
confidence: 99%
“…Premixed, ready-to-use calcium silicatebased endodontic sealers, such as EndoSequence (Brasseler, Savannah, GA, USA) and TotalFill BC Sealer (FKG Dentaire, La Chaux-de-Fonds, Switzerland), have been studied (Zamparini et al 2019). TotalFill BC has adequate physicochemical properties, but appears to be soluble (Poggio et al 2017, Tanomaru-Filho et al 2017, Colombo et al 2018. Recently, the new calcium silicate-based Sealer Plus BC (MK Life, Porto Alegre, RS, Brazil) and Bio-C Sealer (Angelus, Londrina, PR, Brazil) were developed and introduced.…”
Section: Introductionmentioning
confidence: 99%
“…There are no studies done on solubility of endosequence root repair material. EndoSequence Root Repair Material contains many of the same characteristics as BC sealer, with similar chemical composition .study done by poggio et al, showed Endosequence BC sealer showed higher solubility as a result of hydrophilic nanosized particles being present which increases their surface area and allows more liquid molecules to come into contact with them which can be compared with the current study [22].…”
Section: Discussionmentioning
confidence: 52%